Pengembangan Permainan MONESI yang Mengintegrasikan Kearifan Lokal Surabaya Semanggi untuk Melatih Keterampilan Berpikir Kritis - Mas Al dhin Imru'ul Qais As Syauqi; Sunu Kuntjoro; Muji Sri Prastiwi; Eva Kristinawati Putri (LPPM Universitas Pendidikan Mandalika, 2026)
This study aims to develop valid and effective problem-based learning media integrated with the local wisdom of Surabaya clover plants to train students' critical thinking skills, called MONESI (Monopoli Education Semanggi). This study uses a research and development (R&D) method with the ADDIE model, which consists of the analysis, design, development, implementation, and evaluation stages. The subjects of this study were 36 tenth-grade high school students in Surabaya. The research instruments used included a validation sheet and a critical thinking skills test. Data analysis techniques included descriptive validity analysis, Aiken’s V validity index analysis, Cronbach’s alpha reliability test, and Paired-Samples T-Test analysis using IBM SPSS Statistics version 27.0. The results of the study indicate that the MONESI game achieved an average validity score of 3.87 across all assessment aspects, which falls within the high validity (HV) category, with an average validity index of 0.960 (≥ 0.75), while the Cronbach’s alpha reliability test yielded a value of 0.842 (≥ 0.5). Based on these two results, it can be concluded that the MONESI game has a high level of reliability and is suitable for use as a learning medium. Analysis of the critical thinking skills test results using the t-test yielded a significance value of 0.00 < 0.05, indicating a significant improvement in students’ critical thinking skills following the implementation of the MONESI game. This improvement was evident across all critical thinking indicators: interpretation (0.16), analysis (0.23), inference (0.26), explanation (0.27), and evaluation (0.37). Thus, the MONESI game can be considered effective in developing students’ critical thinking skills regarding the topic of water pollution.